The given system of equations is:
1) -8x - 9y = -30
2) -2x - 2y = -8
To solve this system, we can use the method of substitution.
From equation 2), we can express y in terms of x:
-2y = -8 + 2x
y = 4 - x/2
Now we substitute this expression for y into equation 1):
-8x - 9(4 - x/2) = -30
-8x - 36 + 9x/2 = -30
Multiplying the equation by 2 to eliminate fraction:
-16x - 72 + 9x = -60
-16x + 9x = -60 + 72
-7x = 12
x = -12/7
Substituting this value for x back into equation 2) to find y:
-2(-12/7) - 2y = -8
24/7 - 2y = -8
-2y = -56/7 - 24/7
-2y = - 80/7
y = 40/7
Therefore, the solution to the system of equations is x = -12/7 and y = 40/7.
−8x−9y=−30 and minus, 2, x, minus, 2, y, equals, minus, 8−2x−2y=−8.
1 answer